2014
DOI: 10.3168/jds.2013-7802
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplemental progesterone after artificial insemination on expression of interferon-stimulated genes and fertility in dairy cows

Abstract: The objectives of the current study were to evaluate the effects of supplemental progesterone after artificial insemination (AI) on expression of IFN-stimulated genes (ISG) in blood leukocytes and fertility in lactating dairy cows. Weekly cohorts of Holstein cows were blocked by parity (575 primiparous and 923 multiparous) and method of insemination (timed AI or AI on estrus) and allocated randomly within each block to untreated controls, a controlled internal drug release (CIDR) containing 1.38g of progestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 40 publications
(100 reference statements)
2
20
0
5
Order By: Relevance
“…Results from various studies have reported an increase (Monteiro et al 2014), no change (Stevenson et al 2007, Monteiro et al 2015 or a decrease (Parr et al 2014) in pregnancy per AI (P/AI) for cows supplemented with exogenous P4 after ovulation compared with untreated controls. Although several studies evaluated the effect of decreasing P4 concentrations after ovulation on the uterine environment and embryo development (Forde et al 2011, few studies have evaluated the effect of decreasing P4 after ovulation on establishment of pregnancy (Kenyon et al 2013, Carvalho et al 2017).…”
Section: Conceptus Size and Progesterone Studiesmentioning
confidence: 99%
“…Results from various studies have reported an increase (Monteiro et al 2014), no change (Stevenson et al 2007, Monteiro et al 2015 or a decrease (Parr et al 2014) in pregnancy per AI (P/AI) for cows supplemented with exogenous P4 after ovulation compared with untreated controls. Although several studies evaluated the effect of decreasing P4 concentrations after ovulation on the uterine environment and embryo development (Forde et al 2011, few studies have evaluated the effect of decreasing P4 after ovulation on establishment of pregnancy (Kenyon et al 2013, Carvalho et al 2017).…”
Section: Conceptus Size and Progesterone Studiesmentioning
confidence: 99%
“…In addition, another study showed that use of a CIDR insert from 3.5 to 10 days post-insemination increased the circulating progesterone concentration and tended to increase the pregnancy rate [10]. However, a number of studies using CIDR insert treatment post-insemination, in which the timing and duration of CIDR insert use varied, reported no beneficial effects on pregnancy outcomes [182734]. It is unclear why only a few studies have reported beneficial effects on pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that a CIDR insert increased the circulating progesterone concentration [2410]. However, many studies reported no improvement in pregnancy rates [2121834]. Moreover, only a few studies using a CIDR insert post-insemination comprising small numbers of experimental cows reported beneficial effects on pregnancy outcomes [916], indicating the need for more extended field trials.…”
Section: Introductionmentioning
confidence: 99%
“…Conforme descrito anteriormente, foram submetidos ao experimento prático, O resultado para TC60 corrobora com o estudo de Souza (2015), que não obteve diferença na taxa de concepção aos 60 dias. Os resultados de não significância em relação a taxa de concepção tanto aos 30 dias como aos 60 dias também corroboram com outros trabalhos que utilizaram a suplementação de progesterona por implantes intravaginais em diferentes períodos pós IATF (MANN et al, 2001;O´HARA et al, 2013;SOUZA et al, 2013;MONTEIRO Jr et al, 2014;PARR et al, 2014;MONTEIRO-JR et al, 2015;NISHIMURA et al, 2018). Fonte: Dados da pesquisa.…”
Section: Resultados Geraisunclassified
“…Denotaram significante aumento de progesterona sanguínea, porém não obtiveram diferença na taxa de concepção das vacas.Demonstraram, com isso, que a suplementação na 2ª metade da fase luteal não trouxe melhoria na mortalidade embrionária precoce. Vários outros autores(SOUZA et al, 2013;MONTEIRO Jr et al, 2014;O´HARA et al, 2013) observaram efeito negativo da suplementação exógena de progesterona em diferentes situações, tanto com uso de dispositivos quanto com uso de formas injetáveis.Parr et al (2014) observaram diminuição de 12 pontos percentuais na relação de prenhez por inseminação, quando foram utilizados um dispositivo de liberação lenta de progesterona, entre os dias 4 e 9 pós inseminação, em vacas de leite, com um lote tratado em comparação com o grupo controle. Também não foi encontrada diferença na taxa de prenhez dos estudos de Monteiro Jr et al (2015), em que suplementaram vacas com dispositivo intravaginal de progesterona do dia 3 ao dia 20 pós IATF.…”
unclassified